The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/2150135114546203
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Inflammatory Myofibroblastic Tumor

Abstract: Although inflammatory myofibroblastic tumors (IMTs) can be found in virtually every major organ, cardiac origin is rare. After recently providing care to a child who presented with a significant myocardial infarction, interest in this rare tumor was piqued. We describe a comprehensive review of cardiac IMT, including information on nomenclature, epidemiology, clinical features, pathogenesis, gross/histological features, immunohistochemical profile, diagnosis, treatment, and prognosis. Fifty-seven cases were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…In special cases, cardiac surgical intervention such as valve replacement and valvular or vascular reconstruction may be required, and polytetrafluoroethylene grafts are used for bypass grafting. When the tumor is aggressive or there is recurrence in the heart, transplantation may be considered 13 . Based on a good surgical resection and normal post‐resection CT and MRI results, our patient received only ASA and corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…In special cases, cardiac surgical intervention such as valve replacement and valvular or vascular reconstruction may be required, and polytetrafluoroethylene grafts are used for bypass grafting. When the tumor is aggressive or there is recurrence in the heart, transplantation may be considered 13 . Based on a good surgical resection and normal post‐resection CT and MRI results, our patient received only ASA and corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…12 Intracardiac presentations are extremely rare and have a predilection for right-sided cardiac structures. 13 Left-sided intracardiac IMT has been described only in case reports and literature reviews. We found seven case reports of intracardiac IMT involving the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] When we broadened our literature search to include all locations of cardiac IMT, we found two case reports describing systemic embolic phenomenon. 14,21 Eilers et al 13 reviewed 57 published cases of cardiac IMT and found that cardiac IMT occurs throughout the life span but is most commonly found during the pediatric years, with a slight female predominance and most commonly on the right side. Cardiac or constitutional symptoms were described at the most frequent primary presentation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication of this case was reported in World Journal of Pediatric Congential Heart Surgery describing the surgical perspective while this publication was focused on the coronary intervention aspect ( 2 ). When the patient presented with STEMI and a large mass was seen in the LVOT on echocardiogram, the initial diagnosis was embolized vegetation.…”
Section: Discussionmentioning
confidence: 99%